Involving PETN explosive into polyurethane polymer matrix for reactive armour applications. (September 2019) - Elnogomy, Mohamed; Elshenawy, Tamer; Elbeih, Ahmed; Radwan, Mostafa; Yehia, Mohamed; Baraka, Ahmad; Elsayed, Mohamed A.; Gobara, Mohamed
Abstract: This paper describes some formulations of plastic bonded explosives (PBXs) in the form of flexible material (sheet explosive) for military and civilian applications. Different compositions based on (70 wt%, 75 wt%, 78 wt%, 80 wt%) of PETN as high explosive filler were prepared by casting technique using HTPB polyurethane binder material. The production technique of the prepared explosive sheets was described in this research. Sensitivity to impact and friction were also measured. In addition, heat of combustion was determined. Besides, the detonation velocity was measured experimentally and the detonation characteristics were calculated using EXPLO 5 thermodynamic code. For comparison, standard commercial available plastic explosives such as EPX-1 and Datasheet C were studied. By comparing the obtained results, several relationships based on the results were observed. A good agreement between the measured and the calculated results was confirmed. Sample containing 78 wt% of PETN bonded by the polyurethane matrix is an optimum for the application of reactive armours.